Human amnion-derived mesenchymal stem cells attenuate acute lung injury in two different acute lung injury mice models - Wu, Yuxuan; Sun, Hao; Qin, Lianju; Zhang, Xiaomin; Zhou, Hao; Wang, Yao; Wang, Lumin; Li, Meng; Liu, Jiayin; Zhang, Jinsong (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) is one of the most common clinical emergencies with limited effective pharmaceutical treatment in the clinic, especially when it progresses to acute respiratory distress syndrome (ARDS). Currently, mesenchymal stem cells (MSCs) exhibit specific superiority for ALI/ARDS treatment. However, stem cells from different sources may result in controversial effects on similar disease conditions. This study aimed to determine the effects of human amnion-derived mesenchymal stem cells (hAMSCs) on two different ALI mice model. The administered hAMSCs effectively accumulated in the lung tissues in all hAMSC-treated groups. Compared with the model and 1% human serum albumin (HSA) groups, high-dose hAMSCs (1.0×106 cells) group significantly alleviated alveolar-capillary permeability, oxidative stress, inflammatory factors level and histopathological damage. In addition, the NF-κB signaling pathway is one of the key pathways activated during lipopolysaccharide (LPS) or paraquat (PQ)-induced lung injury. Our results indicated that hAMSCs (1.0×106 cells) obviously inhibited the expression of p-IKKα/β, p-IκBα, and p-p65 in the lung tissue (p <0.05). The high-dose (HD) hAMSC treatment exerted beneficial therapeutic effects on ALI mice models without detectable adverse reactions. The therapeutic effect of hAMSCs might involve NF-κB signaling pathway inhibition. hAMSC treatment is a potential candidate therapy for ALI.